Odpowiedzi

2010-03-03T20:57:25+01:00
A) -(-48a² + 10a) - (-4a - a²) dla a = - 1/7
48a²-10a+4a+a²=49a²-6a
49a²-6a=49*(-1/7)²-6*(-1/7)=49*1/49+6/7=1+6/7=13/7
b) -(12 √c - c) + ( -8c + 13 √c ) dla c = 4
-12√c+c-8c+13√c=√c-7c=√4-7*4=2-28=-26
2010-03-03T21:00:32+01:00
A)-(-48a² + 10a) - (-4a - a²) = 48a²-10a+4a+a²=49a²-6a=49(-1/7)²-6*(-1/7)=49* 1/49+ 6/7=1 6/7
b)-(12 √c - c) + ( -8c + 13 √c)=-12√c+c-8c+13√c=√c-7c=√4- 7*4=2-28=-26
2010-03-03T21:02:07+01:00
A) 48a²-10a+4a+a²=49a²-6a
49*(-1/7)-6*(-1/7)=-7+6/7=-6 1/7

b) -12√c+c-8c+13√c=√c-7c
√4-7*4=2-28=-26